2019
DOI: 10.1017/s1047951119000441
|View full text |Cite
|
Sign up to set email alerts
|

Real-world healthcare utilization in adult congenital heart disease: a systematic review of trends and ratios

Abstract: Background:As a result of medical advances, the adult congenital heart disease population is rapidly expanding. Nonetheless, most patients remain prone to increased morbidity and mortality. Therefore, long-term medical resource use is required. This systematic review aims to present the trends over the past decades of medical resource utilization in adult congenital heart disease as well as its current status, with a focus on hospitalizations, emergency department visits, outpatient cardiology visits, and visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…30 Given the increasing numbers and ages of ACHD patients, the demand for healthcare will only increase. 4 , 10 , 33 , 34 Future studies are needed to develop specific pathways to optimize HF care in these patients such that comprehensive management is provided at every HF stage. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Given the increasing numbers and ages of ACHD patients, the demand for healthcare will only increase. 4 , 10 , 33 , 34 Future studies are needed to develop specific pathways to optimize HF care in these patients such that comprehensive management is provided at every HF stage. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…9 However, few studies have reported the contemporary outcomes of ACHD patients after a first hospitalization with HF. 10 , 11 , 12 , 13 , 14 Such data are needed as it would improve allocation of resources and management of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Both the need for life-long monitoring and the increased prevalence of patients with ACHD 3 have resulted in an increased health care utilization. 4 To be able to maintain an adequate and sustainable management of patients with ACHD, noninvasive, objective, and accurate methods to monitor patients are needed. Easily accessible blood biomarkers may be useful in this respect.…”
Section: R Esum Ementioning
confidence: 99%
“…Over the past decades, the absolute number of hospitalizations and outpatient cardiology visits has expanded, showing high and changing healthcare demands for this population. These changes will put an increased burden on the healthcare system and society (Willems et al, 2019). To reduce this, a good understanding of the predictors of high healthcare use is needed.…”
Section: Introductionmentioning
confidence: 99%